Adsorption and desorption properties of total flavonoids from oil palm (Elaeis guineensis Jacq.) mature leaf on macroporous adsorption resins - Che Zain, Mohamad Shazeli; Lee, Soo Yee; Teo, Chian Ying; Shaari, Khozirah (MDPI, 2020)
Three different macroporous resins (XAD7HP, DAX-8, and XAD4) were evaluated for their adsorption and desorption properties in preparing flavonoid-enriched oil palm (Elaeis guineensis Jacq.) leaf extract. The influences of initial concentration, solution pH, contact time, and desorption solvent (ethanol) concentration were determined by static sorption/desorption methods. The optimal condition for adsorption of flavonoids was achieved when the solution of the extract was adjusted to pH 7, reaching equilibrium after 1440 min at 298 K. The adsorption process was well described by a pseudo-second-order kinetics model, while the adsorption isotherm data fitted well with a Freundlich model. The adsorption by each resin was via an exothermic and physical adsorption process. Based on the static experiment results, XAD7HP was found to be the most appropriate adsorbent, while 80% ethanol was the best solvent for desorbent. Further evaluation of its dynamic adsorption and desorption characteristics on a packed glass column showed that XAD7HP could enrich the OPL total flavonoid content by a 3.57-fold increment. Moreover, UHPLC–UV/PDA and UHPLC–MS/MS analysis revealed that apigenin and luteolin derivatives were selectively adsorbed by XAD7HP. Additionally, both the crude OPL extract and the flavonoid-enriched fraction have good DPPH and NO free radical scavenging activities. Multiple interactions between the flavonoids and cross-linked polymeric XAD7HP resin through van der Waals forces and hydrogen bonding described the sorption processes. Therefore, by utilizing this method, the flavonoid-enriched fraction from crude OPL extract could be used as a potential bioactive ingredient in nutraceutical and pharmaceutical applications at minimum cost with optimum efficiency.